2014
DOI: 10.1039/c4tb01552e
|View full text |Cite
|
Sign up to set email alerts
|

DNA protection against ultraviolet irradiation by encapsulation in a multilayered SiO2/TiO2assembly

Abstract: The here presented method allows to protect DNA against UV-induced damage by encapsulating it in a core–shell–shell particulate construct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 47 publications
0
23
0
1
Order By: Relevance
“…The DNA storage system within silica further offers exceptional stability against oxidation (see the reactive oxygen species (ROS) test in the Supporting Information), and by adding an additional titania layer the photoresistance of DNA can be greatly improved. [17] In ancient fossil bone, DNA has the greatest chance of survival if encapsulated within apatite/collagen structures [18] and crystal aggregates, [19] which protect the solid DNA from the environment and humidity-very similar to the encapsulation of DNA within the inorganic silica particles utilized here. Indeed if the decay kinetics presented in Figure 2 for DNA encapsulated in silica are extrapolated to lower temperatures, the data coincides well with the degradation rate of DNA in fossil moa bone derived by Allentoft et al from samples up to 8000 years old.…”
mentioning
confidence: 97%
“…The DNA storage system within silica further offers exceptional stability against oxidation (see the reactive oxygen species (ROS) test in the Supporting Information), and by adding an additional titania layer the photoresistance of DNA can be greatly improved. [17] In ancient fossil bone, DNA has the greatest chance of survival if encapsulated within apatite/collagen structures [18] and crystal aggregates, [19] which protect the solid DNA from the environment and humidity-very similar to the encapsulation of DNA within the inorganic silica particles utilized here. Indeed if the decay kinetics presented in Figure 2 for DNA encapsulated in silica are extrapolated to lower temperatures, the data coincides well with the degradation rate of DNA in fossil moa bone derived by Allentoft et al from samples up to 8000 years old.…”
mentioning
confidence: 97%
“…One possible solution is protecting the DNA code by nanohybridization with ceramic nanoparticles in order to produce a stable nanosystem. [42][43][44][45][46] These encapsulated DNA nanosystems are suitable for code systems. First, they are stable enough to endure severe environments and can maintain information integrity during storage and circulation.…”
Section: Ceramic Nanohybrids With Dna For Bio Codementioning
confidence: 99%
“…Grass and coworkers have developed synthetic DNA "fossils", mimicking the inherent hermetic diffusion barrier of fossils. 17,19,46) DNA was encapsulated into amorphous silica instead of "natural' amber (polymerized terpenes). Silica is a ceramic material with high melting point as well as exceptional barrier property.…”
Section: Design and Synthesis Of Dna@ceramic Nanohybridsmentioning
confidence: 99%
“…The major downside of DNA as a tracer is its limited environmental stability—the biopolymer is prone to chemical decay in the presence of metal ions, non‐neutral pH, strong microbial activity, elevated temperature, and even sunlight . Halter and Zahn, for example, found that DNA has a half‐life of only roughly 2 days in soil .…”
Section: Introductionmentioning
confidence: 99%